2012
DOI: 10.1002/ptr.4605
|View full text |Cite
|
Sign up to set email alerts
|

Stilbenoids from Gnetum macrostachyum Attenuate Human Platelet Aggregation and Adhesion

Abstract: Platelets play a critical role in pathogenesis of cardiovascular disorders and strokes. The inhibition of platelet function is beneficial for the treatment and prevention of these diseases. The phytochemical investigation of stilbenoids from Gnetum macrostachyum Hook. f. led to the isolation of trans-resveratrol (1), isorhapotigenin (2), gnetol (3), bisisorhapontigenin B (4), gnetin C (5), parvifolol A (6), latifolol (7) and gnetuhainin C (8). The isolated stilbenoids were evaluated for in vitro antiplatelet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…the cost for lifetime management of cardiovascular risks (Barrett et al ., ). In this regard, much attention has been given to the development of herbal medicines for preventive treatment against cardiovascular diseases for their merits in safety and nature‐friendly image (Hu ; Kang et al ., ; Park et al ., ; Kloypan et al ., ). The present study has shown that EATN, a neolignan from M. fragrans , inhibited platelet aggregation induced by thrombin and PAF, without affecting platelet damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…the cost for lifetime management of cardiovascular risks (Barrett et al ., ). In this regard, much attention has been given to the development of herbal medicines for preventive treatment against cardiovascular diseases for their merits in safety and nature‐friendly image (Hu ; Kang et al ., ; Park et al ., ; Kloypan et al ., ). The present study has shown that EATN, a neolignan from M. fragrans , inhibited platelet aggregation induced by thrombin and PAF, without affecting platelet damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, chemically synthesized or biologically modified drugs are frequently associated with serious adverse effects, such as internal bleeding and gastrointestinal adverse effects, casting doubt on their health benefit vs. the cost for lifetime management of cardiovascular risks (Barrett et al, 2008). In this regard, much attention has been given to the development of herbal medicines for preventive treatment against cardiovascular diseases for their merits in safety and nature-friendly image (Hu 2003;Kang et al, 2003;Park et al, 2008;Kloypan et al, 2012). The present study has shown that EATN, a neolignan from M. fragrans, inhibited platelet aggregation induced by thrombin and PAF, without affecting platelet damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only a few publications have documented activities of gnetol including strong inhibitory action on tyrosinase, the rate‐limiting enzyme in melanin synthesis, and the ability to inhibit melanogenesis in murine B16 melanoma cells (Ohguchi et al , ). Gnetol has also demonstrated antiplatelet activity (Kloypan et al , ). Additionally, gnetol has shown potential anti‐Alzheimer's disease activity via inhibition of acetylcholinesterase and butyrylcholinesterase (greater activity than resveratrol) (Sermboonpaisam and Sawasdee, ).…”
Section: Introductionmentioning
confidence: 99%